Coronary calcification is associated with elevated serum lipoprotein (a) levels in asymptomatic men over the age of 45 years: A cross-sectional study of the Korean national health checkup data. Issue 9 (5th March 2021) - Chung, Young Hak; Lee, Byoung-Kwon; Kwon, Hyuck Moon; Min, Pil-Ki; Choi, Eui-Young; Yoon, Young Won; Hong, Bum-Kee; Rim, Se-Joong; Kim, Jong-Youn
Abstract : Abstract: Lipoprotein a (Lp (a)) and coronary artery calcification (CAC) are markers of coronary artery and cardiovascular diseases. However, the association between Lp (a) and CAC in asymptomatic individuals remains unclear. In this study, we aimed to determine the influence of Lp (a) on CAC in asymptomatic individuals. We included 2019 asymptomatic Korean adults who underwent testing for a coronary artery calcium score (CACS) and Lp (a) at the Gangnam Severance Hospital Health Checkup Center in Korea from January 2017 to August 2019. Participants were divided into 2 groups: CACS = 0 and CACS > 0. Factors affecting the CACS were analyzed by sex. Because age is a major risk factor for atherosclerosis, ≥45 years in men and ≥55 years in women, we further divided participants into 4 subgroups (≥45 and <45 in men, ≥55 and <55 in women). Factors affecting the CACS in the 4 groups were analyzed. There was a positive correlation between the CACS and traditional cardiovascular risk factors. Lp (a) positively correlated with the CACS in men ( P < .01) and remained significant after multivariable logistic regression ( P < .01). The same result was observed in men aged ≥45 years ( P < .01). Lp (a) is an independently associated factor of CAC and a marker of coronary atherosclerosis in asymptomatic men aged ≥45 years. In asymptomatic men aged ≥45 years, Lp (a) should be measured, and intensive Lp (a)-lowering treatment should be considered.